The Internationalization of Law and Legal Education - Klabbers, Jan.; Klabbers, Jan.; Sellers, Mortimer.; Sellers, Mortimer. (Ius Gentium: Comparative Perspectives on Law and Justice, 2008)
The internationalization of commerce and contemporary life has led to a globalization of legal standards and practices that is beginning to be reflected in legal education. This volume gathers the insights of leading legal scholars from numerous jurisdictions to consider how the culture and the education of their own lawyers serve or should serve the new international reality. Law firms, law schools, universities, courts and other legal institutions must make themselves more "international" to support the national interests of their clients and governments better. This requires new attitudes, new legal rules and new forms of practical instruction. The essays collected in this volume explore the reality of legal globalization and suggest some ways in which the emerging multinational and multicultural legal order could be made more just and effective.